The impact of the five forces and financial market indicators on the market value of the stock - an applied study - Majeed Mohsen Mohammed Al-Ghalbi, (Iraqi Journal for Administrative Sciences, 2024)
The aim of the research is to measure the impact of both the industry environment using indicators alternatives, buyers, sellers, competition, and financial market using a market capitalization indicators, market depth, trading volume and turnover in the market value of the shares, to determine the combined effect and the definition of indicators which have jointly effect on the market value of share,and in the light of the problem of the research on the impact of these forces in the market value, it has been assumed major search hypothesis "there is the significant effect relationship of the industry indicators and indicators of the market environment in the market value of share, can be influential indicators defined jointly from both influencers to define the influence factors." The search use following multiple regression equation: Yij = Bo + SBixi + e ... .xn The research found a positive effect of the share market and the size of the market (market depth), as well as flexibility and market liquidity (stocks turnover) in the market value of the shares, and recommended in combination of indicators and take advantage of the effect of expanding market share of total assets and the size of the market (market depth) for timing of the expansion of equity ,as well as price competition of loans and liquidity of the market (turnover rate) to maximize the value share.